Penguatan jati diri bangsa dalam menghadapi arus globalisasi: Problematika dan pendekatan strategis - Ciptaputra, Chilmi Bagas (Maliki Interdisciplinary Journal, 2025)
National identity plays a crucial role in cultivating shared awareness and reinforcing the unity and cohesion of a nation. In the current age of globalization—characterized by the widespread flow of foreign cultural influences and emerging global values—national identity is increasingly challenged and at risk of erosion. Globalization extends beyond economic and technological domains, impacting cultural, social, and ideological dimensions as well. As a result, national identity becomes fluid, continuously shaped by the interaction between indigenous traditions and global norms. This article explores the critical need to protect and strengthen national identity amid the pressures of globalization. Adopting a qualitative methodology through a literature-based study, it reviews academic works and policy materials related to issues of identity, citizenship, and cultural transformation due to global influences. The core objectives include unpacking the meaning of national identity, assessing how globalization affects national character, and outlining actionable strategies to enhance national identity resilience. The study concludes that building character rooted in Pancasila values, promoting strong national narratives through media, safeguarding local cultural heritage, and encouraging collaboration across sectors are essential efforts. A unified commitment from all levels of society is vital to preserving national sovereignty and integrity in an increasingly competitive global landscape.